STUDI KUALITATIF PEKERJA SEKS KOMERSIAL (PSK) DI DAERAH JONDUL KOTA PEKANBARU TAHUN 2016 - Destrianti, Febri; Harnani, Yessi (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
Commercial Sex Workers (CSW) is one type of professions with social construction experiencing bad and full of stigma to be categorized as the dregs of society. Amount of CSW in Indonesia was 56 thousand and in Riau Province, itâs 2.865 of them. For Jondul area, itâs 36 of CSW. The commercial sex workers are the most vulnerable groups of people from many sides. They are most vulnerable to the spread of various diseases, such as HIV - AIDS, which is a deadly disease as a result of mutually sexual partners. The purpose of this study was to analyze the cause of the woman into commercial sex workers.The design used in this study is a qualitative research with in-depth interview technique. Subjects in this study is using purposive sampling with the key informants are 3 of commercial worker sex and supporter informant are 1 person pimping, 1 residents who live in the jondul area, 1 officer of Lima Puluh Public Health Care and 1 customer.The results show that cause the prostitutes were in Jondul is due to the invitation of friends, but they already know about the work to be done before leaving. The main reason they become prostitutes are economic problems and because of the hurt failed marriage. Knowledge of the prostitutes on the risks and health effects has been quite good. The education level of high-PSK also been included.The results of this research are economic factors and family factors as the main reason they become commercial sex workers. Suggested to health institutions in order to further improve the provision of health information and data collection on the number of prostitutes so that everything can be covered for medical examination.Â